(untitled) (Khairulummah, 2022)
Islamophobia is a psychological state of fear, hatred and prejudice against Islam or Muslims. Under the influence of which Islam is perceived as a geopolitical force or source of violence and terrorism. Consequently, Islam is considered harmful to humanity and is hated. Western critics have tried to create the impression that the existence of Islamophobia in west is just a myth or at most they call it racism. On the other hand, some are calling it the reality of the present time and declaring it purely religious prejudice apart from racism. This article attempts to examine these two views, which will help to reach a conclusion on the issue of whether Islamophobia is simply a form of racism or a religiously based prejudice that is emerged as social phenomenon in the western world.